Mindfulness-Based Functional Therapy: a preliminary open trial of an integrated model of care for people with persistent low back pain - Schütze, Robert; Slater, Helen; O'Sullivan, Peter; Thornton, Jennifer; Finlay-Jones, Amy; Rees, Clare S. (Frontiers in Psychology, 2014)
Objectives: This pilot study investigated the feasibility and clinical utility of implementing a novel, evidence-informed, interdisciplinary group intervention—Mindfulness Based Functional Therapy (MBFT)—for the management of persistent low back pain (LBP) in primary care. MBFT aimed to improve physical and psychological functioning in patients with persistent LBP. Design: A single-group repeated measures design was utilized to gather data about feasibility, effect sizes, clinically significant changes and patient satisfaction. Setting: A community sample of 16 adults (75% female), mean (SD) age 47.00 (9.12) years (range 26–65 years), with mean (SD) LBP duration of 8.00 (9.00) years participated, using a simulated primary care setting at Curtin University in Australia. Intervention: MBFT is an 8-week group intervention co-facilitated by psychology and physiotherapy disciplines. Content includes: mindfulness meditation training, cognitive-functional physiotherapeutic movement retraining, pain education, and group support. Main outcome measures: Several validated self-report measures were used to assess functional disability, emotional functioning, mindfulness, pain catastrophizing, health-related quality of life at baseline, post-intervention, and 6 months follow-up. Results: Adherence and satisfaction was high, with 85% of participants highly satisfied with MBFT. Clinical significance analysis and effect size estimates showed improvements in a number of variables, including pain catastrophizing, physical functioning, role limitations due to physical condition, and depression, although these may have occurred due to non-intervention effects. Conclusions: MBFT is feasible to implement in primary care. Preliminary findings suggest that a randomized controlled trial is warranted to investigate its efficacy in improving physical and emotional functioning in people with disabling persistent LBP.